Oral uptake and persistence of the FnAb-8 protein characterized by in situ radio-labeling and PET/CT imaging - Qian Wang; Wangxi Hai; Sanyuan Shi; Jinliang Peng; Yuhong Xu (Elsevier, 2020)
The absorption of peptides and proteins delivered orally is minimum because of the intestine epithelial barrier. There are few known active transport mechanisms for macromolecules including the neonatal Fc Receptor (FcRn) for the absorption and secretion of IgGs in infant and adult intestine. We had previously described the FnAb-8 protein that could bind to hFcRn tightly at pH 6.0 but barely at pH 7.4. In this study, we examined its uptake, biodistribution and pharmacokinetics after peroral administration in both wild-type and human FcRn transgenic (Tg) mice. FnAb-8 was modified to contain trans-cyclooctene (TCO) which could interact with 18F labeled tetrazine in situ via the bioorthogonal inverse-electron-demand Diels−Alder reaction. We showed that FnAb-8 had a tendency to distribute and persist in the Tg mice intestine for an extended duration of time. It could also be absorbed into the circulation and distributed systemically over a long period of time up to 172 h. The improvement in oral uptake and concentration in the intestine tissue may be valuable for designing oral delivery of biopharmaceuticals, especially for diseases involving the gastric intestinal tissue.